MINERALOGICAL AND PETROGRAPHIC PROPERTIES OF THE HORODYSHCHENSKY MASSIF GABBROS (KORSUN-NOVOMYRHORODSKY PLUTON OF THE UKRAINIAN SHIELD) - Kiriienko, O.; Mitrokhin, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
This research was aimed at compiling data on the mineralogical-petrographic features of the major rocks which are typical of the Horodyshchensky massif to solve the problems of geological differentiation and correlation between the intrusive formations of Korsun-Novomyrhorodsky pluton and to determine the conditions of their formation. Use has been made of mineralogical-petrographic, geochemical and general scientific methods. Previous research results in the field have been amplified with new data on the mineral composition of the Korsun-Novomyrhorodsky pluton gabbroids. In addition, we were the first to identify a number of accessory minerals in the rocks under study: baddeleyite, orthite, monazite, and thorite. The research results showed that the major rock-forming minerals in the studied gabbroids differ in their chemical composition, depending on the petrographic type of rock, zoning of mineral grains, and exsolved microtextures. The obtained data on the mineral composition of the Horodyshchensky massif gabbroids and the variations in the chemistry of rock-forming minerals can be very helpful for studying the geological differentation and correlation between the intrusive formations of Korsun-Novomyrhorodsky pluton as well as clarifying their petrogenesis.
Keywords: anorthosites; norites; feldspar norites; olivine norites; gabbro-anorthosite massifs; Korsun-Novomyrhorodsky pluton; Ukrainian shield